PENGARUH METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP PENINGKATAN MOTIVASI BELAJAR - Sylvie Puspita; Elsye Maria Rosa (Jurnal Keperawatan Notokusumo, 2017)
Background : Student Teams Achievement Division (STAD) is one of cooperative learning methods which is considered as the simplest one, and the best model as a beginning for teachers who just begin to use cooperative app roach. In STAD.This study aims to discover the difference of learning motivation after intervention using STAD learning method is conducted. Method : This study was a quantitative research using quasi-experiment design. The sampling technique was conducted using total sampling. The number of sample in this study was 68 nursing students of semester 6 who were divided into two groups; 34 students in intervention group and 34 students in control group. Result : This study was conducted for three weeks in which STAD learning model was given for three times in the intervention group with the existence of control group. Before the intervention, modules were given to the students. There is a difference motivation between the intervention group and the control group. There is an improvement of motivation on the intervention group. It is proven by the result of T-test on students’ motivation for 0.00 < 0.05. Conclusion : STAD method is one of SCL (Student Centered Learning) learning method which can be applied for the cursing students. Using STAD learning method, learning motivation of the nursing students can be improved.